Treatment of Malaria in Pregnancy: Knowledge of Community Pharmacists in Ibadan, Nigeria (2019)
Purpose: To evaluate the knowledge of community pharmacists in the management of malaria in pregnancy and their adherence to the World Health Organisation (WHO) treatment guidelines. Methods: Questionnaires were administered to obtain information on knowledge and adherence to WHO guidelines. Respondents’ scores on a 12-item knowledge question on the management of malaria in pregnancy were categorized as good knowledge if ≥ 10, and poor knowledge if < 10. Descriptive statistics were used to summarise the data. Chi-square test was used to explore the association between sociodemographic characteristics and knowledge. Results: Pharmacists qualified within 10 years of the study period were 29 (48.3 %). Only 25 (31.3 %) of the pharmacists possessed an additional qualification to Bachelor of Pharmacy degree. Rapid diagnostic test kits (RDT) and light microscopy test (LMT) have been used by 51 (76.2 %) and 17 (28.8 %), respectively, to diagnose malaria. About three-quarters (71.3 %) had poor knowledge of the medication for the treatment of malaria in pregnancy. Knowledge score was neither significantly associated with the pharmacists’ years of qualification (p = 0.174) nor with possession of additional qualification (p = 0.334). Conclusions: There is a substantial gap in pharmacists’ knowledge on the management of malaria in pregnancy, revealing an urgent need for training and adherence of community pharmacists to World Health Organisation treatment guidelines to ensure the safety of pregnant women and the unborn baby.